Modified Masquelet Technique Using Allogeneic Graft for a Gustilo-Anderson Type III-A Open Fracture of the Femur with an 8 cm Bone Defect - Hichem Issaoui; Mohammed Reda Fekhaoui; Moheddin Jamous; Alain-Charles Masquelet (Case Reports in Orthopedics)
The induced membrane technique was initially described by Masquelet et al. in 1986 as a treatment for tibia nonunion; then, it became one of the established methods in the management of bone defects. Several changes have been made to this technique and have been used in different contexts and different methodologies. We present the case of a 16-year-old girl admitted to our department for a polytrauma after a motorcycle accident. She presented a Gustilo III-A open fracture of the right femoral shaft with a large bone defect of 8 centimeters that we treated with a modified Masquelet technique. In the first stage, an Open Reduction and Internal Fixation of the fracture was made using a 4,5 mm Dynamic Compression Plate and a PMMA cement was inserted at the bone defect area. The second stage was done after 11 weeks, and the defect area was filled exclusively with bone allograft from a bone bank. Complete bony union was seen at 60 weeks of follow-up. After the removal of the implants by another surgeon, the patient presented an atraumatic fracture of the neoformed bone that we treated with intramedullary femoral nailing associated with a local autograft using reaming debris. A complete bony union was achieved after 12 weeks with a complete range of motion of the hip and knee. The stability given to the fracture is essential because it influences the quality of the induced membrane and Masquelet has recommended high initial fixation rigidity to promote incorporation of the graft. It is recommended to delay the second stage of this technique after 8 weeks, especially in femoral reconstruction, to optimize the quality of the induced membrane. Several studies used a modified induced membrane technique to recreate a traumatic large bone defect, and all of them used an autologous bone graft alone or an enriched bone graft. In this case, the use of allograft exclusively seems to be as successful as an autologous or enriched bone graft. Now, with the advent of bone banks, it is possible to get an unlimited amount of allograft, so additional research and large studies are necessary before giving recommendations.